The creative hawker center for small - family - business in traditional food of Surabaya - Tanuwidjaja, Gunawan; Daniel, Daniel; Tedjo, Ishak; Karina Brahmana, Ritzky (IPTEK Journal of Proceedings Series, 2017)
The Traditional Food Seller were mostly managed by the family, so they could be categorized as Family Businesses (FB). Furthermore, The FB in traditional food needed integrated business development strategy (related to marketing, business information system as well as architectural design). It was found during the research supported by UBCHEA in Surabaya. One of the strategies needed was to create the legal family food hawker center place quality. The strategy was in line with the Surabaya Municipality Government, The Cooperative and SME’s Business (Dinas Koperasi dan UMKM). A mini hawker center (consisting of 5 hawkers) was proposed in the roadside of the neighborhood collector. Additional to the center, a culinary park was provided onsite for catering the social interactions of Indonesian. The center was designed with creativity, but with low-cost local material such as brick, wood and bamboo. The design was also equipped with clean water, sanitations as well as food storages. All these would create positive branding and ensure sustainability of the hawker center.